Analisis kemampuan komunikasi matematis tertulis pada penyelesaian soal cerita bangun datar peserta didik kelas IV SD Negeri Tegalsari - Novania Dyta Pratiwi; Jenny Indrastoeti Siti Poerwanti; Siti Kamsiyati (Universitas Sebelas Maret, 2023)
This study aims to (1) describe the written mathematical communication skills of fourth grade students in solving flat story problems, (2) describe the factors that influence the written mathematical communication skills of fourth grade students in solving flat story problems. This research is a descriptive qualitative research. The subjects in this study were fourth grade students at SD Negeri Tegalsari. Data collection techniques use the results of test questions and interview results. Data validity testing technique uses time, technique, and source triangulation techniques. The data analysis technique uses Miles and Huberman. The results showed that students' written mathematical communication skills in the ability to write problems in their own language were 50%, the ability to express everyday events with mathematical symbols was 80%, the ability to express everyday problems in the form of pictures was 40%, the ability to understand and evaluate mathematical ideas in solving problems in writing 40%, and the ability to write a conclusion according to the problem 0%. Factors that influence written mathematical communication skills are students' knowledge of the concept of flat shapes, students' confidence in the answers given, understanding of the questions, and the intensity of giving story questions by the teacher